Attitude of women cassava farmers towards participation in growth enhancement support scheme in Oyo state, Nigeria (2016)
The study examined attitude of women cassava farmers towards the Growth Enhancement Support Scheme (GESS) in Oyo state. Three LGAs were purposively selected while random sampling was used to select 4 communities in each LGA with five respondents each using snowball method to give sample size of 180 respondents. Interview schedule was used for data collection and analysed using descriptive and inferential statistics. Results reveal that most of the respondents (67.8%) were within 31-50years of age, married (90.0%), literate (57.8%) with open market (x̅=1.98) and middlemen (x̅=1.78) being the preferred sources of inputs. More than half (52.7%) had over ten years of farming experience, 52.3% cultivated above 6 acres, 68.3% had high level of participation in GESS while 63.3 had favourable attitude towards GESS. Inadequate finance (x̅=1.94) and high illiteracy (x̅=1.93 were the constraints to participation. Significant relationship exists between education (χ2=2.315, p=0.040), level of participation (r=0.258, p= 0.000), sources of input (r=0.223, p= 0.003), constraint to participation (r=0.424, p=0.000) and attitude towards GESS. Though, many respondents were unable to access agricultural inputs from redemption centers yet they had favourable attitude towards GESS. Proper inputs distribution mechanism to eliminate diversion and financial institution with minimum interest rate and collateral should be employed.